Alpha‐mannosidosis: characterization of CNS pathology and correlation between CNS pathology and cognitive function. Issue 4 (4th September 2015) - Borgwardt, L.; Danielsen, E.R.; Thomsen, C.; Månsson, J.E.; Taouatas, N.; Thuesen, A.M.; Olsen, K.J.; Fogh, J.; Dali, C.I.; Lund, A.M.
Abstract : Alpha‐mannosidosis (AM) (OMIM 248500) is a rare lysosomal storage disease. The understanding of the central nervous system (CNS) pathology is limited. This study is the first describing the CNS pathology and the correlation between the CNS pathology and intellectual disabilities in human AM. Thirty‐four patients, aged 6–35 years, with AM were included. Data from 13 healthy controls were included in the analysis of the magnetic resonance spectroscopy (MRS). Measurements of CNS neurodegeneration biomarkers in cerebrospinal fluid (CSF), CSF‐oligosaccharides, and performance of cerebral magnetic resonance imaging (MRI) and MRS were carried out. On MRI, 5 of 10 patients had occipital white matter (WM) signal abnormalities, and 6 of 10 patients had age‐inappropriate myelination. MRS demonstrated significantly elevated mannose complex in gray matter and WM. We found elevated concentrations of tau‐protein, glial fibrillary acidic protein and neurofilament light protein in 97 patients, 74% and 41% of CSF samples, respectively. A negative correlation between CSF‐biomarkers and cognitive function and CSF‐oligosaccharides and cognitive function was found. The combination of MRS/MRI changes, elevated concentrations of CSF‐biomarkers and CSF‐oligosaccharides suggests gliosis and reduced myelination, as part of the CNS pathology in AM. Our data demonstrate early neuropathological changes, which may be taken into consideration when planning initiation of treatment.